Improved method to apportion optical absorption by black and brown carbon under the influence of haze and fog at Lumbini, Nepal, on the Indo-Gangetic Plains - Izhar, Saifi; Gupta, Tarun; Panday, Arnico K. (Environmental pollution (1987), 2020)
Estimates of the brown carbon (BrC) absorption and their contribution to light absorption in ambient aerosols are poorly understood. The existing approaches to apportion light absorption into black carbon (BC) and BrC mainly use the assumption of fixed angstrom absorption exponent (AAE) for BC (1.0), which is not always true for ambient aerosols. Besides, these estimates are seldom validated, leaving significant uncertainty with derived values. Also, BrC absorption studies are largely focused on aqueous extracts, which truly do not represent the aerosolized form, hence the relationship between aqueous extracts and aerosolized form is a subject of research. With this in mind, we collected ambient PM2.5 filter samples at Lumbini, Nepal, at the northern edge of the Indo-Gangetic Plains (IGP) during winter 2017-18. These samples were analyzed for different compositions of carbonaceous aerosol and optical properties. BC and BrC absorptions were derived using a preexisting simplified two-component model but with “improved conditions”. Although BC dominated spectral absorption, BrC contribution for the carbonaceous aerosol absorption increased substantially at ultraviolet wavelengths (example 14.8–53.6% at 365 nm). Further water-soluble BrC absorption value in aerosol was found to be higher by 1.8 times to that obtained in aqueous extracts. Water-soluble OC contributed ∼65% to OC loading and 50% to BrC absorption at 365 nm, indicated the equally important role of water-insoluble organics. Mass absorption efficiency (MAE) of water-soluble BrC in aerosol was found to be 1.7 m2/g, lower to water-insoluble by 2.2 times. High BC MAE was observed which showed positive dependence on secondary coating. Sample collected during events with fog droplets showed a reduction in carbonaceous components loading and light absorption but enhancement in MAE for BrC and BC, signifying that aqueous processing can significantly modify the aerosol optical properties. [Display omitted] •Aerosol optical absorption is apportioned to BC and BrC by using an improved optimization approach.•Water soluble BrC absorption in aerosol was higher by 1.8 times than in aqueous extract.•Water insoluble OC contributed ∼35% of the OC loading but 50% of the BrC absorption.•Elemental carbon constituted high proportion of char compared to soot.•Fog droplet events showed increase in MAE for BC and BrC. An improved and validated approach developed to apportion light absorption by black and brown carbon.